TP8.2.1 Quality Improvement Project: Improving the percentage of patients receiving their consent form copy. (28th October 2021) - Hamid, Mohammed; Elserafy, Amr; Anis, Karim; Dilworth, Mark
Abstract: Aim: Good practice set out by the GMC and DoH is to acquire written informed consent for surgery, despite it not being a legal requirement. Baseline data of 50 consecutive surgical cases, undertaken in the UK's largest trust, found that only 12% of patients were being offered their consent form copy prior to surgery. We constructed a SMART aim to increase this percentage by 20% each month on the general surgical wards of a city hospital. Method: On analysing the patients' physical notes, the three primary drivers identified were factors intrinsic to the department, consent form and our patients; signifying there was a lack of standard awareness, education and safety-net to ensure sustainability. To tackle this in-turn, we designed three PDSA cycles: Departmental seminar and poster, legal education session, and theatre checklist adaptation. Results: Following our first PDSA cycle, the mean percentage increased from 12% to 44%. Using projection analysis, we anticipate this to increase to 76% after the second PDSA cycle, and 100% after PDSA3, with 100% sustainability 1 year later. Conclusions: Overall, our results to-date show that the proportion of patients receiving their consent form copy has improved following our first PDSA cycle, indicating that awareness plays an important role in the consenting process. We predict that education plays an equal role; and given the research supporting the implications of checklists, we forecast that this later element will be the ultimatum leading to 100% sustainability of patients receiving their consent form copy prior to surgery.